Mengembangkan moderasi beragama di kalangan generasi milenial melalui perspektif Perjanjian Baru - Tari, Ezra (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
This writing is motivated by anxiety about interreligious conflicts that are still happening, driven by truth claims regarding the teachings of the holy book, assuming that their religion is the most correct. This is due to misunderstandings and differences of opinion. Exclusive attitudes and a lack of respect for the teachings of other religions still exist among religious people. The purpose of this paper is to provide insight to Christians regarding religious moderation from the perspective of the new covenant for the millennial generation so that Christians have a collective awareness of understanding their own religion. This view invites Christians to prioritize moderation. This paper aims to enlighten the thoughts of Christians, especially the millennial generation. The qualitative-descriptive method was used to analyze the various data obtained. Data analysis can be done through preparation and interpretation activities to draw conclusions. The results of the analysis provide solutions to the millennial generation as the driving force of religious moderation. The effort made is that this generation treats other people first. There are efforts to respect each other, not be exclusive and actively involved, and religious organizations and majority awareness to respect minorities.  AbstrakTulisan ini dilatarbelakangi pada keresahan terhadap konflik antaragama yang masih terjadi, didorong oleh klaim-klaim kebenaran mengenai ajaran kitab suci, menganggap agamanya yang paling benar. Hal ini disebabkan oleh kesalahpahaman dan perbedaan pandangan. Sikap Eksklusif dan kurang meng-hargai ajaran agama lain masih ada di antara umat beragama. Tujuan tulisan ini untuk memberikan wawasan kepada umat Kristiani mengenai moderasi beragama dalam perspektif perjanjian baru bagi generasi milenial, agar umat kristiani memiliki kesadaran kolektif dalam memahami agama sendiri. Pandangan tersebut mengajak orang Kristen lebih mengedepankan sikap moderat. Tulisan ini bertujuan mencerahkan pemikiran umat kristiani, pada khususnya generasi milenial. Metode kualitatif-deskriptif dipakai untuk menganalisis berbagai data yang didapatkan. Analisis data dapat dilakukan melalui kegiatan penyusunan dan penafsiran untuk menyusun kesimpulan. Hasil analisis memberikan solusi kepada generasi milenial sebagai motor penggerak moderasi beragama. Usaha yang dilakukan adalah generasi ini memperlakukan orang lain lebih dahulu diperlakukan. Ada upaya untuk saling menghargai satu sama lain, tidak bersifat eksklusif dan terlibat aktif dan organisasi keagamaan serta kesadaran mayoritas untuk menghargai minoritas.